Assimilation of seismic attenuation model of NW Himalaya and its surrounding region - Vandana; Naresh Kumar (Geosystems and Geoenvironment)
In this study, we analyze the seismic attenuation characteristics of the Northwest Himalaya and adjacent regions using a dataset of 2,716 earthquakes (2.5 ≤ Mw ≤ 5.0) recorded from 2008 to 2015 by a network of 30 broadband seismographs. The single backscattering model was applied to estimate the quality factor of coda waves (Qc) across three lapse time windows (LTWs) at varying frequencies. Our results reveal that Qc increases with both frequency and LTW, suggesting a depth-dependent nature of seismic attenuation in the region. The average attenuation relationships for Qc, Qα and Qβ across the Northwest Himalaya are determined as follows for LTWs of 20, 30, and 40 s, respectively: Qc = (74 ± 14)f (1.27±0.06), Qc = (103 ± 26)f (1.16±0.08), and Qc = (140 ± 41)f (1.10±0.09). Our findings reveal significant variability in Qc, Qα and Qβ across the Tethys (TH), High (HH), Lesser (LH), and Shiwalik (SH) Himalaya regions, as well as the adjacent Indo-Gangetic Plains (IGP), with this variability strongly linked to structural heterogeneity and seismogenic processes in each region. We further establish attenuation relations for distinct tectonic units, observing the following hierarchy: [Qα,β,c−1(HH) < Qα,β,c−1(SH) < Qα,β,c−1(IGP) < Qα,β,c−1(LH) < Qα,β,c−1(TH)]. The Tethys Himalaya exhibits the high attenuation, likely due to its sedimentary structure, while the Higher Himalaya shows the low attenuation. These insights into attenuation characteristics across geotectonic segments in the Northwest Himalaya contribute to a more comprehensive seismic hazard assessment for the region.